2014
DOI: 10.1111/jrh.12070
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access and Use of Infectious Diseases Specialty and General Primary Care Services by Veterans With HIV Infection: Implications for Telehealth and Shared Care Programs

Abstract: Persons with HIV who live far from ID specialty clinics are less likely to use specialty care and more likely to use primary care. Specialty clinics should consider using telehealth to deliver care over distance and programs to coordinate "shared care" relationships with distant primary care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…However, these differences are more likely because the current work captures drive times to HIV care for many urban communities, including those that are in less densely populated metropolitan areas, instead of for single super‐urban cities that may not generalize to all urban locales in the US. This work corroborates notable urban–rural disparities in geographic accessibility to HIV care: rural veterans living with HIV may need to travel much longer to reach primary or specialty HIV care compared to urban veterans living with HIV . Such urban–rural differences in geographic accessibility to HIV care may influence care engagement among PLHIV in urban versus rural US communities .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, these differences are more likely because the current work captures drive times to HIV care for many urban communities, including those that are in less densely populated metropolitan areas, instead of for single super‐urban cities that may not generalize to all urban locales in the US. This work corroborates notable urban–rural disparities in geographic accessibility to HIV care: rural veterans living with HIV may need to travel much longer to reach primary or specialty HIV care compared to urban veterans living with HIV . Such urban–rural differences in geographic accessibility to HIV care may influence care engagement among PLHIV in urban versus rural US communities .…”
Section: Discussionsupporting
confidence: 66%
“…However, the large percentage of PLHIV who have lower incomes and may rely on federally funded programmes to support care delivery suggests that the sample used in the current analysis adequately captures sites providing comprehensive, coordinated HIV care in the US. Further, although our analysis does not include sites primarily serving veterans, our results complement existing literature suggesting that rural veterans living with HIV generally have longer drive times to primary and infectious disease specialty care delivered by the Department of Veterans Affairs . Third, while we selected a 30‐min threshold for comparability to existing primary care thresholds, we acknowledge that there is no universally accepted threshold for suboptimal geographic accessibility in the US, and that geographic accessibility thresholds appropriate for the US may not apply in other settings with different resources, health care systems and geographies.…”
Section: Discussionmentioning
confidence: 66%
“…Patients who are not retained in care report more transportation-related challenges such as transportation costs, unreliable public transportation, and travel distance, as compared with PLWH who are retained in care 34. One study among US Veterans with HIV showed that longer travel time to HIV specialty clinics was associated with decreased use of these clinics 14. PLWH who are out of care face difficulties with scheduling appointments and struggle to consistently attend regular clinic visits.…”
Section: Clinical Usementioning
confidence: 99%
“…97 , 99 Studies evaluating the effect of telehealth models have found similar or even improved HIV and quality-of-life–related outcomes between individuals receiving telehealth HIV care and conventional HIV care. 100–102 …”
Section: Future Directions For Research and Demonstration Projectsmentioning
confidence: 99%